1996
DOI: 10.1210/mend.10.12.8961275
|View full text |Cite
|
Sign up to set email alerts
|

Gonadectomy permits adrenocortical tumorigenesis in mice transgenic for the mouse inhibin alpha-subunit promoter/simian virus 40 T-antigen fusion gene: evidence for negative autoregulation of the inhibin alpha-subunit gene.

Abstract: We have developed a transgenic (TG) mouse model for gonadal tumorigenesis expressing the Simian virus 40 T-antigen (Tag) under the mouse inhibin alpha-subunit promoter. Gonadal tumors appear with 100% penetrance by the age of 5-8 months in the TG mice. When 1-month-old TG mice were gonadectomized, adrenal gland tumors were observed in each animal (12 females, 11 males) at the age of 6-8 months. No adrenal tumors were detected in gonadectomized non-TG mice (nine females, nine males) or in the intact TG mice (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 0 publications
5
56
2
Order By: Relevance
“…Adrenal tumors were found in all the double TG females, even without macroscopic signs of metastases in other tissues, indicating that the tumors were primary and not of metastatic origin. The same conclusion was made earlier as regards adrenal tumors developing in gonadectomized inha/Tag mice (Kananen et al, 1996b).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Adrenal tumors were found in all the double TG females, even without macroscopic signs of metastases in other tissues, indicating that the tumors were primary and not of metastatic origin. The same conclusion was made earlier as regards adrenal tumors developing in gonadectomized inha/Tag mice (Kananen et al, 1996b).…”
Section: Discussionsupporting
confidence: 84%
“…Female bLHb-CTP mice have previously been shown to have hypertrophic adrenal glands, to produce high amounts of corticosterone and to express LHR . In this study, we found adrenal tumorigenesis in the intact double TG bLHb-CTP/Inha/Tag female mice, while in single TG Inha/Tag mice, adrenal tumors develop only after gonadectomy (Kananen et al, 1996b). Owing to the rapid growth of gonadal tumors, in the present study we could not follow the development of adrenal tumors beyond the age of 4-5 months.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Interestingly, the DPC4 gene encodes SMAD4, an important intracellular component of the signalling pathway for the inhibin/activin growth factor family (Kingsley, 1994). Recent evidence from inhibin-α knockout mice (Matzuk et al, 1994) and transgenic mice bearing an inhibin-α promoter Simian virus 40-T antigen transgene (Kananen et al, 1996) implicates the inhibin/activin family in adrenocortical tumorigenesis, with a suggestion that inhibin-α may be a tumour suppressor (Matzuk et al, 1994). Further investigation using microsatellite markers could be used to identify possible changes at these loci.…”
Section: Discussionmentioning
confidence: 99%
“…The ovary produces both inhibin A and B, whereas the testes in all adult males studied to date (men: Illingworth et al, 1996; chimpanzees: Kondo et al, 2000;rhesus monkeys: Mann et al, 1997;Plant et al, 1997;rats: Woodruff et al, 1996; mice: Kananen et al, 1996;hamsters: Jin et al, 2001) secrete inhibin B and there is no evidence of the presence of inhibin A in plasma. However, during development of the testes and in neonatal life, the testes do express mRNA and protein for all three inhibin subunits, α, βA and βB (rats: Tena-Sempere et al, 1999;sheep: Jarred et al, 1999;men: Majdic et al, 1997;Anderson et al, 1998a,b).…”
Section: Introductionmentioning
confidence: 99%